Maintenance Costs and Life Cycle Cost Analysis - Galar, Diego (CRC Press, 2017)
"Authors have attempted to create coherent chapters and sections on how the fundamentals of maintenance cost should be organized, to present them in a logical and sequential order. Necessarily, the text starts with importance of maintenance function in the organization and moves to life cycle cost (LCC) considerations followed by the budgeting constraints. In the process, they have intentionally postponed the discussion about intangible costs and downtime costs later on in the book mainly due to the controversial part of it when arguing with managers. The book will be concluding with a short description of a number of sectors where maintenance cost is of critical importance. The goal is to train the readers for a deeper study and understanding of these elements for decision making in maintenance, more specifically in the context of asset management. This book is intended for managers, engineers, researchers, and practitioners, directly or indirectly involved in the area of maintenance. The book is focused to contribute towards better understanding of maintenance cost and use of this knowledge to improve the maintenance process. Key Features:• Emphasis on maintenance cost and life cycle cost especially under uncertainty.• Systematic approach of how cost models can be applied and used in the maintenance field.• Compiles and reviews existing maintenance cost models.• Consequential and direct costs considered.• Comparison of maintenance costs in different sectors, infrastructure, manufacturing, transport."--Provided by publisher.